2022
DOI: 10.1039/d1sm01795k
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously rotating clusters of active droplets

Abstract: We report on the emergence of spontaneously rotating clusters in active emulsions. Ensembles of self-propelling droplets sediment and then self-organise into planar, hexagonally ordered clusters which hover over the container...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 58 publications
2
37
0
Order By: Relevance
“…Complex collective behavior can result from intricate biological mechanisms but also, can be solely caused by nonequilibrium dynamics (refs. 10 14 have such examples), such that there is a need to untangle physics and biology. To this end, current research in artificial active matter aims to design and develop synthetic microswimmers that can mimic strategies like chemotaxis by purely physicochemical means ( 15 ).…”
mentioning
confidence: 99%
“…Complex collective behavior can result from intricate biological mechanisms but also, can be solely caused by nonequilibrium dynamics (refs. 10 14 have such examples), such that there is a need to untangle physics and biology. To this end, current research in artificial active matter aims to design and develop synthetic microswimmers that can mimic strategies like chemotaxis by purely physicochemical means ( 15 ).…”
mentioning
confidence: 99%
“…The asymmetric trails are likely the cause of the significant lateral motion associated with these droplets, since Marangoni forces arise from asymmetry in interfacial tension gradients, which can be directly attributed to chemical gradients in active droplets. Hokmabad et al [15,22,28] saw similar features in the chemical trails of chaotic active droplets in a dish. In particular, they visualized the formation of a plume of filled micelles using fluorescence and showed that this plume was correlated to droplet reorientation events.…”
Section: Resultsmentioning
confidence: 86%
“…Notably, the settling active droplets were found to undergo transient motion against the direction of gravity. Hokmabad et al [15] have studied the self-assembly of active droplets at the bottom of a dish to form a hexagonal cluster, followed by their spontaneous rise and rotation. Recent theoretical and numerical studies have suggested that an external force field could have a significant impact on active droplet motion [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[42] showed that developing starfish embryos generate different flow patterns during its development process, which determine their self-organisation (formation, dynamics, and dissolution) into living crystals. Analogously, in artificial autophoretic systems, rotational instabilities on the individual scale [10,39] can carry through to the collective dynamics, where we have recently found Pe dependent stability and collective rotation in self-assembled planar clusters [43]. Here, the superposition of self-generated chemical fields might well provide a mechanism for the emergence of stable collective rotational states.…”
Section: Discussion and Outlookmentioning
confidence: 89%